Integrated omics reveals the regulatory role of PKCα in Sertoli cell proliferation and apoptosis through the MAPK/ERK signaling pathway in goose testis - Yupu Song; Qiuyuan Liu; Jingyun Ma; Ichraf Mabrouk; Yuxuan Zhou; Xinyue Li; Guizhen Xue; Xiaoming Ma; Jing Xu; Jingbo Wang; Hongxiao Pan; Guoqing Hua; et al. (Poultry Science)
Testicular development is essential for reproductive performance in geese, as the testes are the primary organs for sperm production and play a pivotal role in egg-laying physiology. Despite their importance, genes, proteins, and pathways regulating goose testicular development are poorly understood. This study employed integrative transcriptomic and proteomic analysis methods to identify critical regulators of testicular development in geese across three reproductive periods. Additionally, the role of PKCα in Sertoli cell proliferation via the MAPK/ERK pathway was evaluated at the cellular level. A total of 8,921 differentially expressed genes and 1,866 differentially expressed proteins were identified, revealing key pathways such as FOXO, MAPK, PPAR, and Hedgehog that regulate testicular development. Both omics correlation analysis and signal pathway regulation network results show the importance of MAPK in this process, while cellular experiment revealed that PKCα affects proliferation and apoptosis of Sertoli cells through the MAPK/ERK signaling pathway. The findings revealed that PKCα downregulation reduced the expression of genes associated with both cell proliferation and apoptosis, resulting in a diminished activity of Sertoli cells.This study compared testicular transcriptomes and proteomes of Hungarian and Jilin white geese, identifying key genes, proteins, and pathways critical for reproduction. These findings advance our understanding of molecular mechanisms underlying testicular development and provide insights to enhance gander reproductive performance.